Overcoming barriers to implementation of patient engagement in clinical trials: feasibility testing of an embedded study - Geneviève Castonguay; Sylvain Bédard; Anick Dubois; Émilie Lessard; Léna Rivard; Ghislaine Rouly; Antoine Boivin (Research Involvement and Engagement)
Abstract Background Patient engagement is attracting considerable interest as a potential strategy to improve the conduct of clinical trials, with evidence of significant improvement in research participant recruitment. However, impact on the retention and adherence of clinical trial participants requires further studies. Embedded studies are specific research designs where a secondary study is “embedded” into a larger host study. We aimed to investigate the feasibility of embedding a study of patient partnership in research, within an ongoing multi-center clinical trial on drug treatment. Methods We developed and embedded a patient engagement intervention (embedded study) into a phase 3 randomized clinical drug trial (host study). The patient engagement intervention consisted of discussions between host study participants and a patient partner, to improve research participants’ experience and retention in the clinical trial. We carried out individual semi-structured interviews with patient partners and other research team members involved in the development and implementation of the embedded study, as well as an analysis of project documents. Data were analyzed using qualitative thematic analysis. Results Factors impacting feasibility and lessons learned for future embedded studies on engagement science were identified. Barriers that curtailed the implementation of patient engagement into an ongoing clinical trial included: the late integration of the embedded study into the host clinical trial, different visions of patient partnership and its potential benefits, differences in communication style and preferences, a lack of fit between the specific needs of the host study and the proposed engagement model, and an overall sense of burden. Integrating patient partners into the host clinical trial was seen as potentially beneficial in improving the experience of participants in the host clinical trial through experience sharing, providing support for the consent process, and improving knowledge transfer. Conclusions This feasibility study offers insights into how contextual factors and decisions made during the design phase can impact the implementation of patient engagement studies embedded in a clinical trial. Findings suggest that knowledge of the clinical trial context (e.g., organizational, administrative, regulatory, ethics) and early collaboration among embedded study and host study teams before initiation of both studies are key conditions for success.